THE CATEGORY OF VOICE IN VIETNAMESE: A SYSTEMIC FUNCTIONAL DESCRIPTION - Hoang, Van Van (VNU Journal of Foreign Studies; Vol 37 No 1, 2021)
This article is a functional description of the category of voice – arguably, one of the most slippery notions in the grammar of Vietnamese that seems to resist any satisfactory treatment. The theoretical framework employed for describing and interpreting the category is Systemic Functional Linguistics (SFL). Three questions which form the basis of this study are: (1) “Does the system of VOICE exist in Vietnamese?”; if so, (2) “What are the delicate options available in the environment of VOICE in Vietnamese?”; and (3) “How can these delicate options be distinguished from the SFL perspective?” The answers to these questions show that unlike formal grammatical descriptions, VOICE exists in Vietnamese as a system; the environment of VOICE opens up a number of delicate options; and these delicate options can be distinguished along the three metafunctions: experiential, interpersonal, and textual. The answers to these questions also show that SFL is a highly relevant framework for describing and interpreting the system of VOICE in Vietnamese: SFL helps us investigate the category from a number of dimensions, enabling us to have a more comprehensive view of it. The study contributes to the application of SFL to the description of Vietnamese grammar - a non-Indo-European language, opening up new potentials for a comprehensive approach to the description of a Systemic Functional Grammar of Vietnamese for research, application, and teaching purposes.